2014
DOI: 10.1245/s10434-014-4123-6
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Desmoplastic Small Round Cell Tumor: Multimodal Treatment Combining Chemotherapy, Surgery, and Radiotherapy is the Best Option

Abstract: DSRCT is a rare and aggressive disease. In patients without EPM, a multimodal treatment combining systemic chemotherapy, complete macroscopic resection, and postoperative WAP RT could enable prolonged survival. No benefit of surgery was demonstrated for patients with EPM. The value of associated hyperthermic intraperitoneal chemotherapy remains unproven.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
130
3
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(158 citation statements)
references
References 39 publications
(54 reference statements)
13
130
3
5
Order By: Relevance
“…This tumor is somewhat alkylator-sensitive, and response seems dose-responsive [31]. Unfortunately, durable responses are limited, and the prognosis for patients remains poor [32]. Median survival ranges from 14 to 25 years [14] with some reports with patients as young as 5 months [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This tumor is somewhat alkylator-sensitive, and response seems dose-responsive [31]. Unfortunately, durable responses are limited, and the prognosis for patients remains poor [32]. Median survival ranges from 14 to 25 years [14] with some reports with patients as young as 5 months [33].…”
Section: Discussionmentioning
confidence: 99%
“…Median survival ranges from 14 to 25 years [14] with some reports with patients as young as 5 months [33]. 3-year overall survival is dismal at around 44% and the 5-year survival rate a dismal 15% [8] with a slightly higher survival reported among those undergoing debulking including 1-2 mm implants [34] of at least 90% of tumor absence of extraperitoneal metastasis [32]. Radiotherapy to high-risk sites, and myeloablative chemotherapy with stem-cell rescue is applied in selected cases especially those with residual disease [31].…”
Section: Discussionmentioning
confidence: 99%
“…To date, the optimal management of DSRCT remains challenging and current schemes lack a significant cure rate despite the use of aggressive treatments (15). Chemoradiotherapy is significant in the treatment of advanced abdominal DSRCT.…”
Section: Case Reportmentioning
confidence: 99%
“…It has a predilection for the serosal surface, most often the abdominal and pelvic cavity. At the time of presentation, up to 50% of the patients may have extra-peritoneal metastasis and even higher rates of local metastasis (2)(3)(4)(5). The most common presenting symptom is abdominal pain, followed by abdominal distention, abdominal mass, and hepatomegaly (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…There is also no reported data on the management of liver metastasis from this disease. Multimodal management including cytoreductive surgery (CRS), chemotherapy, and radiotherapy has been shown to be effective in the treatment of DSRCT (2,3). Also, recent studies have reported the benefit from hyperthermic intraperitoneal chemotherapy (HIPEC) in this disease for intraperitoneal metastatic disease (6).…”
Section: Introductionmentioning
confidence: 99%